Time Costs for Genetic Counseling in Preconception Carrier Screening with Genome Sequencing. Issue 4 (8th February 2018) - Lynch, Frances L.; Himes, Patricia; Gilmore, Marian J.; Morris, Elissa M.; Schneider, Jennifer L.; Kauffman, Tia L.; Shuster, Elizabeth; Reiss, Jacob A.; Dickerson, John F.; Leo, Michael C.; Davis, James V.; McMullen, Carmit K.; et al.
Abstract: Advances in technology and the promise of personalized health care are driving greater use of genome sequencing (GS) for a variety of clinical scenarios. As health systems consider adopting GS, they need to understand the impact of GS on the organization and cost of care. While research has documented a dramatic decrease in the cost of sequencing and interpreting GS, few studies have examined how GS impacts genetic counseling workloads. This study examined the time needed to provide genetic counseling for GS in the context of preconception carrier screening. Genetic counselors prospectively reported on the time spent in the results disclosure process with 107 study participants who were part of the NextGen study. We found that the median time for results disclosure was 64 min (ranged from 5 to 229 min). Preparation work was the most time‐consuming activity. Qualitative data from journal entries, debrief interviews with genetic counselors, and detailed case conference notes provided information on factors influencing time for results disclosure and implications for practice. Results suggest that expanded carrier screening could require significant increases in genetic counseling time, unless we are able to generate new resources to reduce preparation work or develop other strategies such as the creation of new models to deliver this type of service.